Pengaruh Lingkungan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Mediasi:Studi pada Bank Majalengka - Uki, Masduki; Alan Rusdiana; Moch. Febri Sayidil Umam; Pipih Sopiyan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
This study aims to analyze the influence of work environment and organizational culture on employee performance, with organizational commitment as a mediating variable, at Bank Majalengka. A quantitative approach was employed using a survey of all 149 permanent employees, and the data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that the work environment has a significant effect on organizational commitment with a path coefficient of 0.319 (t = 3.984; p = 0.000), while organizational culture has a stronger effect on commitment with a coefficient of 0.488 (t = 7.316; p = 0.000). Organizational culture also directly affects employee performance (coefficient = 0.309; t = 3.171; p = 0.002), as does organizational commitment (coefficient = 0.380; t = 3.313; p = 0.001). However, the work environment does not have a direct effect on performance (coefficient = -0.162; t = 1.817; p = 0.070), but exerts an indirect effect through organizational commitment (mediation coefficient = 0.121; t = 2.570; p = 0.010), indicating full mediation. Additionally, organizational commitment partially mediates the relationship between organizational culture and performance (mediation coefficient = 0.185; t = 2.761; p = 0.006). The R² value for employee performance is 0.568, indicating that 56.8% of the variance in performance is explained by the model. These findings underscore the critical role of organizational commitment as a psychological mechanism linking internal organizational factors to employee performance.